Kendala Orang Tua Dalam Mendampingi Anak Belajar Pada Masa Covid 19 Di Kota Serang - Imas Mastoah Mastoah; Zulaela MS (UIN Sultan Maulana Hasanudin Banten, 2020)
The purpose of the results of this study is to find out more about the problems felt by parents when accompanying children to study at home. Related to the purpose of this study, the effective way of researchers using this type of research is descriptive qualitative type, through interview techniques followed by reducing data and conclusions. In extracting data from this study the researcher was able to produce and show a general picture experienced by parents (respondents) in accompanying children who were unable to study at home during the Covid-19 period, this was extraordinary by draining high anger appetite in a fairly frequent time span. , quota limitations, even parents, especially mothers, are very complaining about the learning given virtually (youtube,) and the results of the provided material such as the Google Class Room followed by evaluations and assignments, this is what raises the anxiety of parents at all. do not understand the material being taught that is delivered via virtual, especially mathematics in grade VI. This needs to be examined together when the current emergency condition is requested for policy makers so that educators, especially for elementary school children, with learning at home do not focus on heavy tasks. This has resulted in the anxiety and confusion of parents whose education cannot be equated with today's world, where it is very difficult to use technology (learning media) such as using Android phones, gadgets. With this research, the researcher tries to make a valuable contribution to further research in exploring the various obstacles faced by parents